(untitled) (Research, Society and Development, 2019)
This article presents an analysis of virtual simulations of Chemistry in some digital repositories, in order to understand if they present properties of experimentation by investigation. The purpose of this analysis was to obtain data in these devices for a reflection of their contributions as digital didactic resources that can foster the academic, social and critical education of the student in high school. For that, three simulations of distinct repositories were analyzed using levels of approximation of an investigative activity according to their pedagogical characteristics. It was found after the analysis that although the simulations present some characteristics of the research experimentation, this is not a methodological focus of these devices, which aim, in turn, to assist in the students’ cognitive construction regarding concepts of Chemistry.